DAYA SAING DESTINASI PARIWISATA KOTA BANDUNG DI ERA ASEAN ECONOMIC COMMUNITY (AEC) - Sukarno Wibowo; Nova Maulidian Hidayat (Barista : Jurnal Kajian Bahasa dan Pariwisata, 2017)
Enforcement of the ASEAN Economic Community (AEC) in principle can provide an opportunity to create a joint economic growth including the tourism sector. Bandung as one of the creative tourism destination should certainly be able to create competitiveness in the face of the ASEAN Economic Community (AEC). As this study shows that tourism destination competitiveness of Bandung city in the ASEAN Economic Community (AEC) needs to be improved, in which aspects of competitiveness, infrastructure development, environmental, technological progress, human resources, openness, and social development. In these problems the development of the tourism sector in the city of Bandung need more promotion. In addition to support promotion agencies, brochures, websites, promotion abroad, and tourism facilities including infrastructure is a contributing factor to increase tourism in the city of Bandung which can contribute significantly to the economic growth of the community. The government must also play a role in the development of tourism. In addition to more consultation with the private sector before formulating new policy, the government is also required to build partnerships with the private sector, improving road safety and health services, as well as a variety of tourism support it.